2015
DOI: 10.1016/j.rasd.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Social competence with an unfamiliar peer in children and adolescents with high functioning autism: Measurement and individual differences

Abstract: Children and adolescents with high functioning autism (HFA) display heterogeneity in social competence, which may be particularly evident during interactions with unfamiliar peers. The goal of this study was to examine predictors of social competence variability during an unfamiliar peer interaction. Thirty-nine participants with HFA and 39 age-, gender- and IQ-matched comparison participants were observed during dyadic laboratory interactions and detailed behavioral coding revealed three social competence dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…This may be indicative of the great heterogeneity of anxiety levels in children and adolescents with HFA: some may be characterized as extremely withdrawn and fearful, while others are described as approach-oriented and unafraid (Burnette et al, 2011; Wing & Gould, 1979). A recent study found that levels of social anxiety related to social skills in an interaction with a novel peer in a sample of children and adolescents with HFA, indicating the ecological importance of understanding the relationships between these constructs (Usher, Burrows, Schwartz, & Henderson, 2015). The wide heterogeneity in levels of Fear and Shyness may relate to adaptive functioning in real-world contexts with unfamiliar peers.…”
Section: Discussionmentioning
confidence: 99%
“…This may be indicative of the great heterogeneity of anxiety levels in children and adolescents with HFA: some may be characterized as extremely withdrawn and fearful, while others are described as approach-oriented and unafraid (Burnette et al, 2011; Wing & Gould, 1979). A recent study found that levels of social anxiety related to social skills in an interaction with a novel peer in a sample of children and adolescents with HFA, indicating the ecological importance of understanding the relationships between these constructs (Usher, Burrows, Schwartz, & Henderson, 2015). The wide heterogeneity in levels of Fear and Shyness may relate to adaptive functioning in real-world contexts with unfamiliar peers.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the number of variables in subsequent analyses, consistent with previous practices used in our laboratory (Usher et al 2015), inter-relations among observed behavioral codes were examined using Principal Component Analysis (PCA; Abdi and Williams 2010). Variables were entered into a PCA using a Varimax rotation and a two-factor solution was specified.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that temperamental dimensions relating to social desirability and social motivation, such as affiliation, relate to behavior similarly for individuals with and without ASD (Burrows et al 2016). There was also a lack of information on co-occurring diagnoses of anxiety or depression, which could potentially impact adolescents' perceptions and metaperceptions (Pozo et al 1991), as well as their observed social behavior (Usher et al 2015). Examining these various potential sources of individual differences in metaperception abilities in both ASD and TD groups would strengthen future work in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it was determined that high level of social phobia (concern for being criticized) negatively affected life of individuals, and high level of perceived social competence created a positive effect upon individuals (Connolly, 1989;Baltacı & Hamarta, 2013;Erözkan, 2011;Márquez, Martín, & Brackett, 2006). Furthermore, because the individuals with high level of concern for being criticized as the most important indicator and sub-dimension of social phobia felt themselves under threat socially, they were noticed to have low competence perceptions related to coping with social problems (Usher, Burrows, Schwartz, & Henderson, 2015;Thomasson & Psouni, 2010).…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%